2011
DOI: 10.1038/mt.2011.69
|View full text |Cite
|
Sign up to set email alerts
|

Virally delivered Channelrhodopsin-2 Safely and Effectively Restores Visual Function in Multiple Mouse Models of Blindness

Abstract: Previous work established retinal expression of channelrhodopsin-2 (ChR2), an algal cation channel gated by light, restored physiological and behavioral visual responses in otherwise blind rd1 mice. However, a viable ChR2-based human therapy must meet several key criteria: (i) ChR2 expression must be targeted, robust, and long-term, (ii) ChR2 must provide long-term and continuous therapeutic efficacy, and (iii) both viral vector delivery and ChR2 expression must be safe. Here, we demonstrate the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
247
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(261 citation statements)
references
References 46 publications
(62 reference statements)
9
247
3
2
Order By: Relevance
“…However, the practical engineering of a high-acuity prosthetic system is highly non-trivial and will require the integration of real-time image-processing for emulating the ganglion-cell encoding of the visual stimuli 39,15 (which generally includes a diversity of response types 40 ), high-resolution eyetracking 39 and real-time hologram computations. Major challenges also remain on the optogenetic probe engineering front-including testing of strategies for safe and effective cellular transfections 7 , and the exploration of favourable red-shifted alternatives to ChR2 (whose excitation peak is effectively absorbed by pigments of the macula lutea in humans 41 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the practical engineering of a high-acuity prosthetic system is highly non-trivial and will require the integration of real-time image-processing for emulating the ganglion-cell encoding of the visual stimuli 39,15 (which generally includes a diversity of response types 40 ), high-resolution eyetracking 39 and real-time hologram computations. Major challenges also remain on the optogenetic probe engineering front-including testing of strategies for safe and effective cellular transfections 7 , and the exploration of favourable red-shifted alternatives to ChR2 (whose excitation peak is effectively absorbed by pigments of the macula lutea in humans 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…This could be highly desirable for neuro-photonic applications of optogenetic technology 1,2 including optogenetic retinal prostheses [3][4][5][6][7][8][9] , because sensory information is generally represented in distributed spatio-temporal patterns of activity carried across large populations of neurons, while neighbouring neurons in real circuits are often found to have widely divergent response properties. Although electrical retinal prostheses are already being used to aid blind human subjects, it appears that their ultimate performance/resolution may be limited by current spread, and the acuity of B20/2,000 is common to both 60 electrode epiretinal and 1,500 electrode sub-retinal systems.…”
mentioning
confidence: 99%
“…25 Viral delivery of ChR2 to ON bipolar cells has recently been described. 51 Gene expression with current AAV serotypes and/or promoters is not yet efficient in human ON bipolar cells. 52 has not yet been achieved.…”
Section: Strategies For Optogenetic Restoration Of Visionmentioning
confidence: 99%
“…However, this is a fast moving field and better vectors are not too far away. 51 AAV-based or other means of restricting expression of optogenetic tools to AII cells or ON-versus-OFF ganglion cells have not yet been reported.…”
Section: Strategies For Optogenetic Restoration Of Visionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] Expression of channelrhodopsin in RGCs might allow greater spatial resolution and acuity than that achieved with current prosthetic devices. This has motivated a large body of proof-of-concept studies in rodents and other small animals, which have shown the feasibility of the approach, [7][8][9][10][16][17][18] and a first-in-human phase 1 clinical trial was initiated recently (ClinicalTrials.gov NCT02556736). However, the use of genetically encoded opsins for vision restoration has several setbacks in terms of clinical development.…”
Section: Introductionmentioning
confidence: 99%